El levantamiento indígena de 1846 en Santiago Nonualco. Conflictos locales, etnicidad y lucha de facciones en el Salvador - López Bernal, Carlos Gregorio (2000)
This essay analyzes indigenous revolts in el Salvador in the first half of the nineteenth century, especially the indigenous uprising of 1846 in Santiago Nonualco, takin in to consideration local conflicts, ethnic factors, and the weakness of the state  apparatus.